The category of “now” in Husserl’s time phenomenology and in recentivism - Bańka, Józef (Folia Philosophica, 2007)
The subject of comparison of Husserl’s category of “now” with the category of “now” functioning in recentivism constitutes the notion of “living reality” in the sense of embroiling “now” into the activity of the stream of consciousness. In Husserl’s conception, this „living reality” falls apart into retention and protention. Hence, we deal with the passage of subsequent “nows”, taking nunc stans, which creates all other time- and logic-delayed objects for granted. This lack of an ontological foundation of the category of “now” in Husserl’s conception removes recentivism. In recentivism, though, the category of “now” constitutes punctum saliens (that is fluidity) on the one hand, and characterises being as newly formed each time, that is an event which in its new “now” is continually taking on the new otherness on the other hand. It is enough for an event to “be”, but “the way” it is is no longer dependent on the event, but a phenomenon which phenomenology would like to ignore. At best, it would like to eliminate it as insignificant.